A review of literature on open innovation in small and medium-sized enterprises - Mokter Hossain (Journal of Global Entrepreneurship Research, 2015)
Studies on open innovation in small andmedium-sized enterprises (SMEs) have experienced a rapid growth over the last several years. Yet, there is no comprehensive review on this field of research. The objective of this study is to examine current research on open innovation in SMEs to integrate empirical findings and to point out future research agenda. Findings suggest that studies are mostly performed based on panel data and only several studies include sophisticated statistical analysis. Studies aremostly conducted in the European context along with some studies in China and Korea while studies in the context of North America are scant. Open innovation improves the overall innovation performance of SMEs. However, relevant theories and models formanagers are not well-established in the literature.
Keywords: 650; Open innovation; SMEs; Network; Strategy; Literature review